THE GROWTH OF SENGON AND NILAM ON LOAMY SAND SOIL IN AGROFORESTRY SYSTEM - Aris Sudomo (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2007)
Research of loamy and soil influence on growth ofagroforestry sengon and nilam was conducted in private forestland in Sukamulih Vilage, Sariwangi Sub-Distric, Tasikmalaya District on November 2004 to November 2006. Two kinds ofsoil sample were taken from the upper and down part ofprivate forestland area. The research was conducted by analizing those soil samples in the laboratory. The result shows that the private forest land has loamy sand soil its texture with low rate offerlility. The planting activity was conducted in 3 blocks ofplanting area and 48 sengon were ptanted each block. The diameter and height ofsengon tree in loamy sand soil have good rate ofgrowth, which is 7.28 in of height and 9.48 of diameter in 24 months old. Meanwhile, nilam has 64.32 cm of height, 141.68 branches and 2.9 ofwet weight in 3 months old after cutting in the monoculture planting puttern. The loamy sond soil texture gives the positive influence on sengon and nilam growth. Therefore sengon and are potentially to developedin private forest development and degraded forestland rehabilitation.